Diagnosis, treatment and transmission of rifampicin-resistant TB in the Netherlands, 2010-2019 - de Vries, G; Akkerman, O; Boeree, M; van Hest, R; Kamst, M; de Lange, W; Magis-Escurra, C; Meijer, W; van Soolingen, D (The international journal of tuberculosis and lung disease, 2023)
New tools for diagnosis and treatment of rifampicin-resistant (RR-) and multidrug-resistant (MDR-) TB have become available in the last decade, including better tests confirming transmission. To analyse transmission risks of MDR/RR-TB in the Netherlands. Analysis of national data of patients with MDR/RR-TB notified in 2010-2019, including contact investigation and genotyping data. Patients with MDR/RR-TB ( = 121) were more often female (adjusted odds ratio [aOR] 1.5), foreign-born, previously treated for TB (aOR 5.2) and co-infected with HIV (aOR 2.3) than patients with no MDR/RR-TB. Treatment outcomes were satisfactory, with at least 79% completing treatment. After additional whole-genome sequencing (WGS), five molecular clusters of 16 patients remained. Patients in three clusters could not be epidemiologically linked and were unlikely to have been infected in the Netherlands. The remaining eight (6.6%) patients with MDR/RR-TB belonged to two clusters, and were likely the result of transmission in the Netherlands. Among close contacts of patients with smear-positive pulmonary MDR/RR-TB, 13.4% ( = 38) had TB infection and 1.1% ( = 3) had TB disease. Only six contacts with TB infection were treated with a quinolone-based preventive treatment regimen. MDR/RR-TB is effectively controlled in the Netherlands. Preventive treatment options could be considered more frequently in contacts clearly infected by an index patient with MDR-TB.